Charles Valentine Riley. Founder of modern entomology - González, Jorge M. (Anartia, 2020)
The Joint Commission of the Scientific Societies of Washington had its Annual Meeting on January 18, 1896, just a few months after the unexpected death of Charles Valentine Riley (C.V. Riley). The event started with a memorial lecture in appreciation of the gifted polyglot, artist, poet, writer, philosopher, naturalist, inventor, politician, teacher, and scientist. “The name of Charles Valentine Riley is known in every part of the world where there are naturalists or intelligent agriculturists” was the first sentence pronounced (Brown Goode, 1896).